The Impact of Social Media on Brand Value Growth - MIHAELA IOANA GURĂU; IVONA STOICA (RĂPAN); MARIANA GURĂU (Global Economic Observer)
The phenomenon of social media marketing (SMM) has only been developed in the last decade and focuses mainly on the impact that social networks have on consumer behavior. Despite the fact that each social media network has its own characteristics, the ubiquitous impact on economic life can create a chain of consequences that cause interactions between networks, ending up as one network exerts its influence on the others. The approach adopted in this research brings new perspectives for the literature by analyzing how an influencer works on building their own branding, which helps him to be asked by other businesses for promotion and, why not, to help build other brands. We will therefore highlight how influencers can harness the potency of social networks and profit in favor of their own image.